CRISPR/Cas9-Mediated Editing of Autophagy Gene 6 in Petunia Decreases Flower Longevity, Seed Yield, and Phosphorus Remobilization by Accelerating Ethylene Production and Senescence-Related Gene Expression - Lin, Yiyun; Jones, Michelle L. (Frontiers in Plant Science, 2022)
Developmental petal senescence is a type of programmed cell death (PCD), during which the production of ethylene is induced, the expression of PCD-related genes is upregulated, and nutrients are recycled. Autophagy is an intracellular mechanism involved in PCD modulation and nutrient cycling. As a central component of the autophagy pathway, Autophagy Gene 6 (ATG6) was previously shown as a negative regulator of petal senescence. To better understand the role of autophagy in ethylene biosynthesis and nutrient remobilization during petal senescence, we generated and characterized the knockout (KO) mutants of PhATG6 using CRISPR/Cas9 in Petunia × hybrida ‘Mitchell Diploid’. PhATG6-KO lines exhibited decreased flower longevity when compared to the flowers of the wild-type or a non-mutated regenerative line (controls), confirming the negative regulatory role of ATG6 in petal senescence. Smaller capsules and fewer seeds per capsule were produced in the KO plants, indicating the crucial function of autophagy in seed production. Ethylene production and ethylene biosynthesis genes were upregulated earlier in the KO lines than the controls, indicating that autophagy affects flower longevity through ethylene. The transcript levels of petal PCD-related genes, including PhATG6, PhATG8d, PhPI3K (Phosphatidylinositol 3-Kinase), and a metacaspase gene PhMC1 were upregulated earlier in the corollas of PhATG6-KO lines, which supported the accelerated PCD in the KO plants. The remobilization of phosphorus was reduced in the KO lines, showing that nutrient recycling was compromised. Our study demonstrated the important role of autophagy in flower lifespan and seed production and supported the interactions between autophagy and various regulatory factors during developmental petal senescence.